Lift and drag coefficients behavior at low Reynolds number in an airfoil with miniflaps gurney submitted to a turbulent flow: part 2 - Colman Lerner, Jorge León (2010)
Following the work performed in Part 1, new wind tunnel experiments were conducted in order to investigate the influence of different sizes of Gurney mini-flaps upon the aerodynamic behavior of a low Reynolds number airfoil HQ 17. The airfoil, with and without the Gurney mini-flaps, are immersed in a low Reynolds number turbulent flow. Lift and drag coefficients were calculated for the plain wing and for the wing with mini-flaps of 1%, 1.5%, 2% and 2.5% height of the chord and plotted as a function of the angle of attack (α). The experimental data, including the power density spectrum of the instantaneous longitudinal and vertical velocities and load, show that the Gurney mini-flap acts enhancing the lift coefficient of the airfoil coupled with an increased drag, primarily due to the particular mini-flaps wake structure. We also found that the airfoil performance, for the four mini-flaps tested, is almost independent of the scales of the incoming turbulence.